Determinan Harga dan Potensi Sampah sebagai Sumber Modal Ekonomi di Bank Sampah Syariah UINSA Surabaya - Lusiana Dewi; Ummi Hanik; Habibah Awwaliah; Ana Toni Roby Candra Yudha (Nomicpedia: Journal of Economics and Business Innovation, 2021)
The purpose of this study is to analyze the factors that influence the price of waste at the UINSA Sharia Waste Bank. The research method used this time is descriptive qualitative. The data were collected using direct and in-depth observation techniques in the field to find out what factors influence the fluctuation of waste prices. Researchers also use documentation methods to support the achievement of research results. The results show that the price of waste every time it deposits to collectors is always different. The management always asks the collectors why the price of waste often fluctuates, but the collectors always answer because the price is determined from the center. The relevant suggestion that can be used is that it is recommended that the UINSA Sharia Waste Bank be a partner of the waste collection center, because there is little possibility of periodic price changes.